Politicians, governed vs. non-governed interest groups and rent dissipation - Gil S. Epstein; Yosef Mealem (Bar-Ilan University, Department of Economics, 2013)
Government intervention often gives rise to contests and the government can influence their outcome by choosing their type. We consider a contest with two interest groups: one that is governed by a central planner and one that is not. Rent dissipation is compared under two well-known contest success functions: the generalized logit and the all-pay auction. We also consider the case in which the government can limit the size of the non-governed interest group in order to determine the scope of rent dissipation, with the goal of either increasing the rent obtained by the government or reducing the wasted resources invested in the contest.
Keywords: D70; D71; D72; 330; rent dissipation; central planner; contest; all-pay auction; generalized logit contest success function